2018
DOI: 10.1155/2018/9561413
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated with Hydatidiform Mole among Patients Undergoing Uterine Evacuation at Mbarara Regional Referral Hospital

Abstract: Objective We sought to determine the prevalence of and factors associated with hydatidiform molar gestations amongst patients undergoing uterine evacuation at Mbarara Regional Referral Hospital (MRRH), Mbarara, Uganda. Methods This was a cross-sectional study carried out from November 2016 to February 2017. All patients admitted for uterine evacuation for nonviable pregnancy were included. The study registered 181 patients. Data were collected on sociodemographics, medical conditions, obstetrics, and gynecolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 14 publications
2
28
1
1
Order By: Relevance
“…Itis possible that the prevalence of CT infection reported in our study represents a true picture of the disease since the reported condom usage was very low, which may suggest further investigation of other risk behaviors like non-monogamous spouses [15]. In contrast to our finding, higher rates of CT infection were reported in women attending gynecology clinics in Mbarara, Uganda (26.5%) [16], Jos, Nigeria (51.6%) [17]and South Eastern Nigeria(40.7%) [18]. However, lower rates of CT was reported in Western Kenya (3%) [19], North Western Nigeria(9.6%) [15]and Iran (8.3%) [20].…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…Itis possible that the prevalence of CT infection reported in our study represents a true picture of the disease since the reported condom usage was very low, which may suggest further investigation of other risk behaviors like non-monogamous spouses [15]. In contrast to our finding, higher rates of CT infection were reported in women attending gynecology clinics in Mbarara, Uganda (26.5%) [16], Jos, Nigeria (51.6%) [17]and South Eastern Nigeria(40.7%) [18]. However, lower rates of CT was reported in Western Kenya (3%) [19], North Western Nigeria(9.6%) [15]and Iran (8.3%) [20].…”
Section: Discussioncontrasting
confidence: 88%
“…Similar findings have been reported in other studies [12, 22]. In contrast with previous literature, marital status [15] and other factors that might be associated with CT, including urban residence [16], multiple sexual partners [8], and pre-marital sex were not found to be significant risk factors in this study. In Ethiopia, it was difficult to obtain information regarding sexual behavior because of socio-cultural inhibitions.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A study, by Oliver M et al, found that 13 patients with ultrasound scan diagnosis of molar pregnancy who underwent suction curettage, only 9 (69.2%) were confirmed to be complete moles [10].…”
Section: Discussionmentioning
confidence: 99%
“…2,5 A study in Ibadan found the prevalence of Chlamydia cervicitis to be 17.6% among women undergoing hysterosalphingography for infertility evaluation while several studies have proven that C. trachomatis infections rates are higher among infertile than fertile women. 3,[5][6][7][8][9][10][11][12][13][14][15] Patients with positive Chlamydia assay are 1.7 times at risk of infertility compared with patients with negative assay. 5 A study reported that Chlamydia trachomatis IgG was significantly higher among patients presenting with infertility than those that did not.…”
Section: Introductionmentioning
confidence: 99%